OPTIMIZATION OF CULTURAL CONDITIONS FOR EXTRACELLULAR KERATINASE PRODUCTION BY BACILLUS SPECIES ISOLATED FROM POULTRY FARM SOIL - RADHIKA SUDHIR MEHTA; RIDDHI JAYANT JHOLAPARA; CHHAYA S. SAWANT (International Journal of Pharma and Bio Sciences, 2013)
Poultry industry waste contains a major proportion of feathers, which comprise mainly of keratin.Keratin is an insoluble, fibrous protein, which makes the feathers resistant to proteolytic enzymes. Several microorganisms can carry out the degradation of such complex substrates. The present study exploits the ability of soil bacteria to degrade feather wastes. Bacteria can degrade feather keratin with their enzyme: keratinase. By screening poultry farm soil samples, two feather degrading isolates were obtained which showed degradation of 1% feathers within 7 days. On the biochemical identification and 16S rRNA sequencing, the isolates showed 99% homology with Bacillus licheniformis and Bacillus subtilis. Medium optimization for maximum enzyme production was performed. The optimized conditions showed significant increase in enzyme production, as determined by the activity i.e. 14.344U/ml/min for B. licheniformis and 12.934U/ml/min for B. subtilis. The study shows the potential of the isolates to carry out eco-friendly disposal of feathers.